Pain relief for reduction of acute anterior shoulder dislocations: a prospective randomized study comparing intravenous sedation with intra-articular lidocaine - Cheok, C.Y.; Mohamad, J.A.; Ahmad, T.S. (Lippincott, Williams & Wilkins, 2011)
Objectives: The aim was to compare the effectiveness of intra-articular lidocaine (IAL) versus intravenous Demerol and Diazepam (IVS) in reduction of acute anterior shoulder dislocation.